قوّة الحجاج في تبليغ مقاصد الخطاب السياسي –خطاب المرحلة الانتقاليّة للقايد صالح أنموذجا- - وفاء, قصاد; عبد الحكيم, سحالية (جامعة الوادي - University of Eloued, 2022)
الملخص يحظى الخطاب السياسي بمكانة ذات امتياز في حياة الفرد والمجتمع، خاصة حين يرتبط بالنشاطات الإنسانية المختلفة ﴿الدينيّة، الاجتماعيّة، الاقتصاديّة...﴾ فهو رسالة هادفة لما يحمله من دلائل قويّة ومعان مركّزة حين يؤطرها برنامج حجاجي مدروس يحقق للخطاب خصوصيته . ويعتبر خطاب المرحلة الانتقاليّة للقايد صالح من بين أهم الخطابات السياسيّة التي عنيت بتوجيه الحراك الشعبي، ودفعه إلى ضبط مطالبه انطلاقا من إتباع مسار حجاجي كفيل بتبليغ مقاصده. وفي هذا السياق تعود هذه الورقة البحثية إلى قراءة تداوليّة تسعى إلى استنباط آليّات البناء الحجاجي الهادفة إلى تبليغ مقاصد خطاب المرحلة الانتقاليّة وبيان مرتكزاته الحجاجيّة. The political discourse enjoys a privileged position in the life of the individual and society, especially when it is related to the various human activities - religious, social, economic ... It is a purposeful message due to its strong indications and focused meanings when framed by a deliberate argumentative program that achieves the discourse's specificity. The speech of the transitional period of Gaid Salih is considered one of the most important political speeches that was concerned with directing the popular movement and pushing it to control its demands based on following the path of argumentative who is a guarantor of communicating his aims. In this context, my article returns to a pragmatics reading that seeks to devise the mechanisms of argumentative construction aimed at communicating the aims of the transitional period discourse and showing its argumentative foundations
مقال
Keywords: الخطاب السياسي ; الحجاج ; المقاصد ; المرحلة الانتقاليّة ; الحراك الشعبي.